Anatomical and radiological evaluation of less invasive stabilisation system (LISS) in correlation with knee lateral collateral ligament insertion. (November 2017) - Freimoser, Florian; Grechenig, Stephan; Ofenhitzer, Anna; Bakota, Bore; Staresinic, Mario; Pfeifer, Christian G.
Abstract: Introduction: The Less Invasive Stabilisation System (LISS) is an angle-stable plate that enables treatment of distal femoral comminuted and periprosthetic fracture. As it is placed through a minimally-invasive lateral approach, lateral knee pain is a commonly described symptom after its application. This study investigates knee lateral collateral ligament (LCL) iatrogenic injury during LISS plate fixation. A cadaver study was performed and a retrospective radiological investigation with the analysis of its clinical application was conducted to evaluate possible knee LCL damage. Methods: The cadaver study included 13 human lower extremities, treated with LISS. After application, lateral knee side was dissected, implants were removed and distances between the drill holes and LCL origin were measured. In the retrospective radiological evaluation, postoperative X-rays for patients treated with distal femoral LISS plate in the University Hospital Regensburg, Germany from January 2010 to December 2015 were examined. Following a protocol described by Pietrini et al ., the LCL origin on postoperative X-rays was calculated, both in lateral and anterior-posterior (AP) view, and distances between the plate and its closest locking screw to the LCL origin were measured. Results: In the cadaver study, the mean distance between the closest drilling hole and the ligament origin was 14.0 mm (range 9–21 mm; SD 3.8 mm). Twenty-two patients matched the inclusion criteria for the retrospective radiological study. In lateral view, the mean distance between the origin and the closest locking screw was 6.3 mm (range 0–16.4 mm; SD 4.7 mm); the mean distance between the origin and the plate was 3.1 mm (range 0–13.9 mm; SD 4.1 mm). In AP view, the mean distance between LCL origin and the nearest screw was 2.4 mm (range 0–7.6 mm; SD 2.4 mm). The mean distance between the origin and the most distal locking screw was 9.2 mm (range 0–17.5 mm; SD 4.0 mm). Discussion: The LISS is a safe option to treat distal femoral fractures in respect to the LCL. Due to close proximity, the LCL might be harmed; therefore, lateral knee pain or lateral instability after implantation should be assessed in further treatment.